Sustainability Through a Green Event (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
The London summer Olympics and Paralympics 2012 set the first mark in history to become unique and hold the critical strands of sustainability events. This paper discusses a sustainable event held by Cleanfix-Schevaran Systems Private Limited at Nanjangud taluk, Mysuru district, Karnataka elaborating the pre-event planning, monitoring during event, and post-event data analyses.  Net zero Objective was achieved through  Zero energy skylight (40 numbers) and 40 turbo vent fans, 25KW solar and the carbon laid from travel made by participants from all over the world was taken to neutrality through carbon sequestration (~39.97T) with bio-mass of ~14.69 T planned at the site, which is beyond existing plantation accounting to ~17T. 62 species of plants belonging to 32 families are potential carbon neutralizers. Others points were use of eco-friendly VOC’s-free prints of ecosolvent, digital displays, single-use bottles replaced with reusable glass bottles, ceramic plates, and local catering with native food, factory has been designed water positive, with ponds conserving rainwater and a sewage treatment plant. Overall, the event gives an insightful way forward for government agencies, industries, institutions, event management agencies and communities that engage in several occasions and events annually.